Knowledge, attitudes, and practices regarding drug-drug interactions among community pharmacists in Santa Cruz, Manila - Aquino, Michael John L.; Lui, John Patrick C.; Onza, Maria Michaela G.; Robles, Yolanda (Manila: Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2023)
Potential drug-drug interactions (DDIs) were observed in 8% of medications prescribed to adult Filipinos at a clinic in a government hospital. Studies show that community pharmacists have suboptimal knowledge on common DDis, and practices in handling potential DD0s was poor leading to an increased rate of undetected DD0s. In the Philippines, pharmacists' detection of potentially clinically significant DDls was rarely focused on. This study then aims to assess the levels of knowledge, attitudes, and practices regarding common DDls of community pharmacists from Santa Cruz, Manila. This is a descriptive, cross-sectional mixed methods study that used an anonymous survey questionnaire, and interview. Pharmacists exhibited moderate knowledge, positive attitudes, and fair practices. Linear Regression Analysis showed no significant association in KAP among demographic groups, and between knowledge, attitude, and practice levels. Kruskal-Wallis Test, Mann-Whitney U Test, and Chi-square test showed no significant difference in knowledge, attitude, and practice levels among demographic groups. Thematic analysis showed that participants may not have a systemic approach to handling patients and varying methods of handling DDls (i.e., using online DDI checkers, personal knowledge, and probing). Heavy workload, fatigue, and time constraints contribute to the transfer of responsibility in addressing DDIs to physicians. Capacity building and more efficient and accessible DDI checkers can help in preventing harm from adverse DDls from ever-reaching the patient. The KAP levels of community pharmacists in Santa Cruz, Manila, and various barriers in handling clinically relevant DDI may compromise medication safety. As prevention of DDI is the responsibility of all HCPs, the problem of DD0s can be addressed at the prescriber level by promoting physicians' knowledge of potentially harmful DD0s. Continuing education, the use of software programs, and a systemic approach to handling patients can help in improving the knowledge, attitudes, and practice of handling DDIs in the field of community pharmacy.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, August 2023.
Keywords: Drug Interactions -- Knowledge -- Manila (Philippines); Pharmacists -- Attitudes -- Manila (Philippines); Pharmacists -- Practices -- Manila (Philippines)